PFOS Disturbs BDNF-ERK-CREB Signalling in Association with Increased MicroRNA-22 in SH-SY5Y Cells. (15th November 2015) - Li, Wu; He, Qing-zhi; Wu, Cheng-qiu; Pan, Xiao-yuan; Wang, Jing; Tan, Yan; Shan, Xiao-yun; Zeng, Huai-cai
Abstract : Perfluorooctane sulfonate (PFOS), a ubiquitous environmental pollutant, is neurotoxic to mammalian species. However, the underlying mechanism of its neurotoxicity was unclear. We hypothesized that PFOS suppresses BDNF expression to produce its neurotoxic effects by inhibiting the ERK-CREB pathway. SH-SY5Y human neuroblastoma cells were exposed to various concentrations of PFOS to examine the role of the BDNF-ERK-CREB signalling pathway in PFOS-induced apoptosis and cytotoxicity. Furthermore, to ascertain the mechanism by which PFOS reduces BDNF signalling, we examined the expression levels of miR-16 and miR-22, which potentially regulate BDNF mRNA translation at the posttranscriptional level. Results indicated that PFOS significantly decreased cell viability and induced apoptosis in SH-SY5Y cells. In addition, BDNF and pERK protein levels decreased after PFOS treatment; however, pCREB protein levels were significantly elevated in PFOS treated groups. TrkB protein expression increased in the 10 μ M and 50 μ M PFOS groups and significantly decreased in the 100 μ M PFOS group. Our results demonstrated that PFOS exposure decreased miR-16 expression and increased miR-22 expression, which may represent a possible mechanism by which PFOS decreases BDNF protein levels. PFOS may inhibit BDNF-ERK-CREB signalling by increasing miR-22 levels, which may, in part, explain the mechanism of PFOS neurotoxicity.